Mapping of Low-Frequency Raman Modes in CVD-Grown Transition Metal Dichalcogenides: Layer Number, Stacking Orientation and Resonant Effects - MCEVOY, NIALL; COLEMAN, JONATHAN; DUESBERG, GEORG (My University, 2016)
Layered inorganic materials, such as the transition metal dichalcogenides (TMDs), have attracted much attention due to their exceptional electronic and optical properties. Reliable synthesis and characterization of these materials must be developed if these properties are to be exploited. Herein, we present low-frequency Raman analysis of MoS2, MoSe2, WSe2 and WS2 grown by chemical vapour deposition (CVD). Raman spectra are acquired over large areas allowing changes in the position and intensity of the shear and layer-breathing modes to be visualized in maps. This allows detailed characterization of mono- and few-layered TMDs which is complementary to well-established (high-frequency) Raman and photoluminescence spectroscopy. This study presents a major stepping stone in fundamental understanding of layered materials as mapping the low-frequency modes allows the quality, symmetry, stacking configuration and layer number of 2D materials to be probed over large areas. In addition, we report on anomalous resonance effects in the low-frequency region of the WS2 Raman spectrum.
PUBLISHED
Keywords: transition metal dichalcogenides (TMDs); transition metal dichalcogenides (TMDs)